Kanski's clinical ophthalmology : a systematic approach - Salmon, John F. ([[Amsterdam] : Elsevier, 2025)
Through eight outstanding editions, Kanski's Clinical Ophthalmology has been the classic specialty textbook, providing the perfect ophthalmology foundation for trainees and a valuable reference source for experienced practitioners. Building on the previous edition by Dr. Brad Bowling, Dr. John Salmon from Oxford University has comprehensively revised the textbook. The 10th Edition retains Dr. Kanski's highly effective format of succinct text and visually dynamic presentation, providing authoritative, focused guidance on the diagnosis and management of ophthalmic disorders. Extremely well organized and comprehensive in scope, this visually stunning book reflects the latest advances in the field, facilitating quick comprehension to enhance learning, aid exam preparation and guide clinical practice. As a general ophthalmic textbook, this is the gold standard.--Provided by publisher.
Examination techniques -- Eyelids -- Lacrimal drainage system -- Orbit -- Dry eye -- Conjunctiva -- Cornea -- Corneal and refractive surgery -- Episclera and sclera -- Lens -- Glaucoma -- Uveitis -- Ocular tumours -- Retinal vascular disease -- Acquired macular disorders -- Hereditary fundus dystrophies -- Retinal detachment -- Vitreous opacities -- Neuro-ophthalmology -- Ocular tumors -- Ophthalmic side effects of systemic medication -- Trauma.
Preceded by Kanski's clinical ophthalmology : a systematic approach
Includes index.
Keywords: Diagnostic Techniques, Ophthalmological; Eye Diseases; Ophthalmology